Developing an ivory-like material for stereolithography-based additive manufacturing. (June 2021) - Rath, Thaddäa; Martl, Otmar; Steyrer, Bernhard; Seidler, Konstanze; Addison, Richard; Holzhausen, Elena; Stampfl, Jürgen
Highlights: 3D printable ivory substitute material for a more efficient restoration process. Colour, translucency and density of the substitute are comparable to ivory. Mechanical properties are similar to natural ivory with a transversal orientation. Post-processing with handcraft techniques provides an even more natural appearance. Abstract: Through history, numerous art, religious and every-day objects were carved from ivory because of its aesthetic appearance, convenient workability and its durability. Since the ivory trading ban was passed in 1989, many natural and synthetic materials were introduced as a replacement, but these are typically only available in bulk. To restore sometimes very complex and delicate artefacts, it is economically reasonable to develop a substitute that can be built by additive manufacturing to reduce carving time and material waste. Such a substitute material should especially mimic the aesthetic characteristics of ivory by means of the colour, translucency and surface gloss. All merchantable 3D printable substitute materials have evidential limitations in exactly those important characteristics. The newly developed substitute material called "Digory" is processible with an additive manufacturing technique that derived from stereolithography. Layer by layer, a photosensitive slurry that consists mainly of a dimethacrylic resin filled with calcium phosphate particles is polymerized with a UV laser. The solids loading, which was adjusted to fit the translucency of ivory, was around 30 vol.%. At this content, the density of about 1.79 g cm −3 and the hardness of 35.7 HV0.2 are equivalent to the values for ivory found in the literature. Small quantities of yellow and red colour pigments were used to modify the basic colour. With further post-processing using traditional handcraft techniques, such as staining and polishing of the surface, an optical imitation of natural ivory was achieved. Graphical abstract: Image, graphical abstract